1996
DOI: 10.1002/(sici)1096-8644(199601)99:1<175::aid-ajpa10>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of weight gain, hand/wrist maturation; and dental emergence rates in chimpanzees aged 0–24 months from varying captive environments

Abstract: Variability during the first 2 years of growth and development is examined in captive chimpanzees. The mixed longitudinal study of 175 animals compares curves of weight, hand/wrist maturation, and dental emergence for groups within the sample which differ in sex, rearing circumstances (mother-reared versus hand-reared), and colony (Primate Foundation of Arizona, White Sands Research Center, and The University of Texas M.D. Anderson Cancer Center Department of Veterinary Sciences in Bastrop, Texas). Comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Finally, it has been suggested that nonhuman primates that are born and raised in captivity show more rapid skeletal, dental, and sexual development than wild animals (e.g., PhillipsConroy and Jolly, 1988;Kahumbu and Eley, 1991;Marzke et al, 1996;Kelley and Smith, 2003;Zihlman et al, 2004). Zihlman et al (2004) demonstrated this for ages at maxillary molar eruption in chimpanzees, and Phillips- Conroy and Jolly (1988) found the same results for maxillary and mandibular teeth in wild and captive baboon populations.…”
Section: Incremental Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, it has been suggested that nonhuman primates that are born and raised in captivity show more rapid skeletal, dental, and sexual development than wild animals (e.g., PhillipsConroy and Jolly, 1988;Kahumbu and Eley, 1991;Marzke et al, 1996;Kelley and Smith, 2003;Zihlman et al, 2004). Zihlman et al (2004) demonstrated this for ages at maxillary molar eruption in chimpanzees, and Phillips- Conroy and Jolly (1988) found the same results for maxillary and mandibular teeth in wild and captive baboon populations.…”
Section: Incremental Developmentmentioning
confidence: 93%
“…Assessments of the skeletal and dental development of chimpanzees have been underway since before the beginning of the twentieth century (Keith, 1899;Selenka, 1899), continuing today in both captive and natural environments (e.g., Kraemer et al, 1982;Goodall, 1986;Anemone et al, 1991Anemone et al, , 1996Kuykendall, 1996;Marzke et al, 1996;Zihlman et al, 2004). Hominoid dental development and tooth emergence have historically been valued because they offer insight into theories of life history and phylogeny (Zuckerman, 1928;Krogman, 1930;Schultz, 1935;Bennejeant, 1940;Clements and Zuckerman, 1953;Gavan and Swindler, 1966;Gavan, 1967), as well as the absolute ages of individuals that are still developing their dentitions (e.g., Garn et al, 1959;Bailit, 1976;Dean and Wood, 1981;Smith et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Long bones develop from the epiphyseal growth plates at the proximate and distal ends (Hinchliffe & Johnson, 1980); cartilage cells at these growth plates transduce mechanical stimuli into extracellular matrix production (Lovejoy et al, 1999). These stimuli are believed to simultaneously build bone, yet prevent the epiphyses from ossifying prematurely (Marzke et al, 1996). The result is that bone architecture is modelled in response to the environment such that bone is built in areas subjected to stress and reabsorbed in areas without stress, a phenomenon known as Wolff's Law (Wolff, 1891;Salter, 1970).…”
Section: Morphological Developmentmentioning
confidence: 99%
“…Within the systems of growth, development and maturation, skeletal maturation is probably the least studied system in chimpanzees (exceptions are Watts 1971;Marzke et al 1996, on infants younger than 24 months of age; Matsuzawa et al 1990, on wild chimpanzees; Hamada et al 1998). Based on radiographs collected at the Yerkes laboratory, Watts (1971) presented the chimpanzee norm of RUS skeletal maturation based on the TW1 method.…”
Section: Discussionmentioning
confidence: 99%